Benchmarking of purchasing practices using Kraljic approach. Issue 7 (3rd October 2016) - Gangurde, Sanjaykumar R.; Chavan, Amol A.
Abstract : Purpose: The purpose of this paper is to reduce impact on profit and supply risk, for strategic part by defining appropriate purchasing strategies using Kraljic portfolio model (KPM) approach. Design/methodology/approach: A five-step approach of KPM is used to identify strategic parts. The attributes affecting impact on profit and supply risk are then identified. A structured questionnaire is prepared for each attribute. Likert scale having weights from 1 to 5 is used to select method of measurement for each response. The overall score of attributes for dimensions "supply risk" and "impact on profit" interpret the position of the part, i.e., "strategic part, " "leverage part, " "bottleneck part" or "non-critical part" in the Kraljic matrix. The part having highest impact on profit and supply risk is to be considered as strategic part for defining the purchasing strategies. Findings: This paper outlines a practical solution to the problem of designing/defining purchasing strategies for development of supplier. Impact on profit is reduced by cost reduction and quality improvement whereas supply risk reduced by improving delivery time and suppliers profile. Research limitations/implications: The proposed methodology is applied to a boiler industry to identify the strategic parts and focus on strategic suppliers, which are fewer in number but having larger impact on profit and supply risk. The "Body" part of ball valve assembly of the boiler is considered for the study. However, it can be extended for selecting and evaluating of suppliers strategy for other parts of the boiler. Not only boiler industry sector but also other companies also benefit from the results of this study by implementing the purchasing strategies as formulated in the KPM. Originality/value: The Kraljic matrix has been largely used in many different industries like automobile, manufacturing, construction, oil and gas, etc., as an efficient tool for developing differentiated purchasing strategies. However, its application on parts procured by boiler industry is unknown, as well as the lack of systematical approach on criteria prioritization which is one of the key issues of the methodology. This work explores the output usefulness and its applicability on ball valve assembly projects.